Implementation of the Role of Peacemakers in Bridging Differences in Beliefs: A Christian Educator's Perspective - La'ia, Dewi; Santo, Joseph Christ (Didache: Journal of Christian Education, 2025)
Indonesia is a nation significantly rich in cultural, ethnic, and religious diversity. While this diversity is a source of strength, it also presents challenges in fostering social harmony. This study examines the implementation of the peacemaker concept in bridging differences in beliefs, based on Jesus' teachings in Matthew 5:9. Using a qualitative method with a literature review approach (library research), the research explores relevant websites, journals, and books to analyze the biblical meaning of "peacemakers" and how Christian educators can apply this principle in Indonesia’s religiously plural society. Findings indicate that being a peacemaker requires active engagement in fostering peace rather than merely living in passive harmony. Key implementation strategies include developing interfaith empathy, applying conflict mediation techniques rooted in Christian values, and adopting a collaborative approach to community service. This study concludes that Christian educators play a vital role as peacemakers, with a responsibility to bridge differences, facilitate interfaith dialogue, and promote tolerance and inclusivity within Indonesia’s diverse society.